Studi Kelayakan Bisnis Pendidikan: Kajian Literatur - Rodhiyatul Khoirani; Nadila Aisyah Azzahra; Syarifah Mahfuzoh (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyse the business feasibility of education through economic, market, legal, technical, and financial aspects, using a literature review methodology. The data sources consist of secondary data obtained from scientific journal articles, previous research findings, policy reports, and academic documents relevant to the management of educational businesses. The literature analysed was selected based on criteria of topic relevance to the business feasibility study of education, source credibility, and a publication span of the last ten years to ensure the findings remain relevant to current conditions. The analysis was conducted by examining and comparing a number of selected articles to identify patterns, dominant factors, and interrelationships between aspects that influence the success of educational enterprises. The results of the analysis indicate that economic aspects influence public purchasing power and the stability of an institution’s income; market aspects determine opportunities for sustainability through demand levels and competition; legal aspects ensure legal compliance and operational certainty; technical aspects relate to the readiness of infrastructure and human resources; whilst financial aspects are the primary determinant through budget planning, cost management, and funding sources. Thus, a business feasibility study for an educational institution serves as the basis for strategic decision-making to minimise risk and ensure the sustainability of the institution.